"You Are Really at Their Mercy": Examining the Relationship between Transportation Disadvantage and Social Exclusion among Older Adults through the Use of Innovative Technology. Issue 7 (July 2019) - Fields, Noelle; Cronley, Courtney; Mattingly, Stephen P.; Murphy, Erin R.; Miller, Vivian J.
This study investigates transportation disadvantage (TD) and its impact on social exclusion among lower-income older adults ( n = 10) through the use of a custom-designed daily transportation diary app, MyAmble . The study utilized an ecological momentary assessment design using the Travel Buddy, which was the qualitative feature of MyAmble . The Travel Buddy allowed study participants to share their transportation experiences as they relate to the following domains of social exclusion: quality of life, participation, and resources. Conventional content analysis revealed five primary themes related to TD and social exclusion: constrained autononmy and flexibility, safety concerns, dimished emotional well-being, barriers to community engagement, and burdensome. The Travel Buddy produced qualitative data that contextualize lost opportunities and how characteristics of economic justice exacerbate the risk of TD, as well as how individuals manage within these intersections of disadvantage. Study findings provide insight for expanded conversations about how to transform transportation planning from mobility to equity . Finally, the use of ecological momentary assessment through digital platforms such as the Travel Buddy offer an innovative way to collect holistic data related to TD that will lead to better opportunities for transportation planners, engineers, and social service providers to work together to address the needs of environmental justice populations, including lower-income older adults.